2020
DOI: 10.1093/qjmed/hcaa039.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effect of calcium chloride in combination with neostagmine and atropine against residual neuromuscular blockade at the end of general anesthesia

Abstract: Background Muscle relaxants used in general anesthesia during the insertion of an endotracheal tube (ETT) to relax the muscles of the neck and throat, which reduces the risk of injury. They also are used to relax the chest muscles when an endotracheal tube is used to aid mechanical ventilation. Objective The aim of this study has been to evaluate the effect of calcium chloride coadministered with neostigmine and atropine on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Similarly, another recent study also found administration of 5 mg/kg of calcium chloride after neostigmine improves the neuromuscular recovery by increasing the TOF ratio at 5 and 10 min and reducing the PORC. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another recent study also found administration of 5 mg/kg of calcium chloride after neostigmine improves the neuromuscular recovery by increasing the TOF ratio at 5 and 10 min and reducing the PORC. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%